Divergence and Redundancy in CSLD2 and CSLD3 Function During Arabidopsis Thaliana Root Hair and Female Gametophyte Development - Yoo, Cheol-Min; Quan, Li; Blancaflor, Elison B. (Frontiers in Plant Science, 2012)
The Arabidopsis cellulose synthase-like D (CSLD) 2 and 3 genes are known to function in root hair development. Here, we show that these genes also play a role in female gametophyte development because csld2 csld3 double mutants were observed to have low seed set that could be traced to defects in female transmission efficiency. Cell biological studies of csld2 csld3 ovules showed premature synergid cell degeneration during megagametogenesis and reduced pollen tube penetration during fertilization. Although CSLD2 and CSLD3 function redundantly in female gametophyte development, detailed analyses of root hair phenotypes of progeny from genetic crosses between csld2 and csld3, suggest that CSLD3 might play a more prominent role than CSLD2 in root hair development. Phylogenetic and gene duplication studies of CSLD2 and CSLD3 homologs in Populus, rice, Physcomitrella and Selaginella were performed to better understand the partial redundancy and divergence of these two genes. Our results indicate that the ancestor of land plants contained only two copies of CSLDs, one of which developed into the CSLD5 lineage in flowering plants, and the other formed the CSLD1/2/3/4 clade. In addition, CSLD2 and CSLD3 likely originated from a recent genome-wide duplication event explaining their redundancy. Moreover, sliding-window dN/dS analysis showed that most of the coding regions of CSLD2 and CSLD3 have been under strong purifying selection pressure. However, the region that encodes the N-terminus of CSLD3 has been under relatively relaxed selection pressure as indicated by its high dN/dS value, suggesting that CSLD3 might have gained additional functions through more frequent non-synonymous sequence changes at the N-terminus. which could partly explain the more prominent role of CSLD3 during root hair development compared to CSLD2.